Acid proteinase, phospholipase, and biofilm production of Candida species isolated from blood cultures - KARAHASAN, AYŞEGÜL; ÇERİKÇİOĞLU, NİLGÜN (SPRINGER, 2007)
Three virulence factors comprising proteinase, phospholipase, and biofilm among 68 Candida albicans and 31 non-albicans Candida strains (11 C. tropicalis, 8 C. parapsilosis, 6 C. glabrata, 4 C. guillermondii, 2 C. krusei) isolated from blood cultures were analyzed. In total, 61 (89.7%) C. albicans strains were detected as proteinase positive whereas eight (25.8%) non-albicans Candida strains were proteinase positive (P < 0.05). Phospholipase production was detected in 41 (60.3%) C. albicans strains. All non-albicans Candida strains were phospholipase negative. Biofilm production was determined by both visual and spectrophotometric methods. Eight (11.8%) of C. albicans strains and 13 (41.93%) of 31 non-albicans Candida strains were biofilm positive with two of the methods (P < 0.05). According to our results, we may suggest that detection of hydrolytic enzyme and biofilm production abilities of the Candida isolates in clinical mycology laboratories may warn the clinican for a possible hematogenous infection.
Keywords: virulence; Candida; blood; SLIME PRODUCTION; INFECTIONS; STRAINS